2018
DOI: 10.1002/jcb.27597
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter 2.5 induced bronchial epithelial cell injury via activation of 5′‐adenosine monophosphate‐activated protein kinase‐mediated autophagy

Abstract: The impact of particulate matter 2.5 (PM2.5) on the respiratory system is a worldwide concern. However, the mechanisms by which PM2.5 causes disease are still unclear. In this study, we investigated the effect of PM2.5 on autophagy and studied the effect of PM2.5-induced autophagy and 5'-adenosine monophosphate-activated protein kinase (AMPK) on cell proliferation, cell cycle, apoptosis, reactive oxygen species (ROS), and airway inflammation using human bronchial epithelial cells 16HBE140 cells. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…Several stimuli activated the AMPK signaling pathway in different cells. Long et al found that PM2.5 increased the activation of the AMPK pathway and autophagy in bronchial epithelial cells [35]. We also found that PM 1649b exposure promoted the activation of the AMPK pathway.…”
Section: Discussionsupporting
confidence: 75%
“…Several stimuli activated the AMPK signaling pathway in different cells. Long et al found that PM2.5 increased the activation of the AMPK pathway and autophagy in bronchial epithelial cells [35]. We also found that PM 1649b exposure promoted the activation of the AMPK pathway.…”
Section: Discussionsupporting
confidence: 75%
“…Lai et al 30 exposed A549 cells to DEP, urban dust and black carbon and found a significant increase in autophagy as indicated by the conversion of LC3I to LC3II. Long et al 14 demonstrated that exposure of bronchial cells to 2.5 µm PM induced autophagy by overexpressing Atg5 and beclin-1, increasing the ratio of LC3I to LC3II proteins and increasing autophagosome formation. Bai et al 12 showed that PM 1 (1 μm) at a concentration of 100 μg/mL induces autophagy and intracellular oxidative stress in type II alveolar epithelial cells in a dose-dependent manner.…”
Section: Scientific Reports |mentioning
confidence: 99%
“…One mechanism that cells use for defence against oxidative stress is autophagy, which is a homeostatic process that reduces cytoplasmic volume by degrading damaged organelles and proteins through a lysosome-dependent degradation process, and new organelles and proteins are synthesized as replacements 9-11 . Previous studies have emphasized that exposure to PM induces the generation of reactive oxygen species (ROS) and increases the levels of autophagy and cell death [12][13][14] . Some of the most harmful components of urban PM are derived from diesel exhaust particles (DEP) 15,16 .…”
mentioning
confidence: 99%
“…A cellular defense mechanism against oxidative stress is the phenomenon of autophagy, which is a homeostatic aeration that reduces the cytoplasmic volume by degrading organelles and proteins damaged in the cell. Thus, a lysosome-dependent degradation process occurs, and new organelles and proteins are synthesized in substitution [ 118 , 119 , 120 ]. Previous studies demonstrated that the exposure to PM induces the formation of reactive oxygen species (ROS) and increases levels of autophagy and cell death [ 120 , 121 ].…”
Section: Effects Of Air Contaminants On Epithelial Cells Of the Lungmentioning
confidence: 99%